2022
DOI: 10.3892/mmr.2022.12616
|View full text |Cite
|
Sign up to set email alerts
|

Pinus thunbergii bark extract rich in flavonoids promotes hair growth in dorsal skin by regulating inflammatory cytokines and increasing growth factors in mice

Abstract: Korean maritime pine bark ( Pinus thunbergii ) has been used as an alternative medicine due to its beneficial properties, including anti-inflammatory effects. To date, the anti-inflammatory and hair growth-promoting effects of Pinus densiflora bark extract have remained elusive. Therefore, in the present study, Pinus thunbergii bark was extracted with pure water (100°C) and the extract was examined to determine its polyphenol and flavonoid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Among these, flavonoids have been found to be the most effective in promoting hair regeneration in BalB/c mice (Rambwawasvika et al, 2019). In vivo experiments have shown that flavonoids, such as the flavonoid-rich extract of Pinus thunbergii bark, can also promote hair regeneration, which promotes hair growth in C57BL/6 mice by regulating the expression of inflammatory substances and promoting growth factors (Her et al, 2022). Similarly, the addition of flavonoid-rich extract of Equisetum hyemale L. was found to promote hair regrowth in Sprague Dawley rats with chemically-induced alopecia (David et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, flavonoids have been found to be the most effective in promoting hair regeneration in BalB/c mice (Rambwawasvika et al, 2019). In vivo experiments have shown that flavonoids, such as the flavonoid-rich extract of Pinus thunbergii bark, can also promote hair regeneration, which promotes hair growth in C57BL/6 mice by regulating the expression of inflammatory substances and promoting growth factors (Her et al, 2022). Similarly, the addition of flavonoid-rich extract of Equisetum hyemale L. was found to promote hair regrowth in Sprague Dawley rats with chemically-induced alopecia (David et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some extracts alleviated inflammatory response determined by the expression levels of inflammatory cytokines, such as tumor necrosis factor-alpha (TNFα), interleukin (IL)-1β, and IL-6 [59,65,67,98], or cellular senescence determined by the expression level of senescence-associated β-galactosidase (SA-β-gal) [61,65,67] in cells stimulated with phorbol-12-myristate 13-acetate (PMA) plus calcium ionophore A23187 [50], H 2 O 2 [59,61,65], or androgen [67]. The anti-inflammatory effects of extracts of Angelica gigas and Pinus thunbergii were shown by the reduced levels of pro-inflammatory cytokines (TNF-α and IL-1β) and increased levels of anti-inflammatory cytokines (IL-4 and IL-13) in the dorsal skin of mice [50,108]. In silico molecular docking analysis of phytochemical components of Leea indica resulted in the identification of several compounds with high ligand efficiencies towards prostaglandin D 2 synthase, implicating their potential anti-inflammatory activity [103].…”
Section: Antioxidant Anti-inflammatory and Anti-senescence Effects Of...mentioning
confidence: 99%
“…As a general mechanism, many herbs, higher plants, and their active constituents used for the management of alopecia target the hair cycle - keratinocyte proliferation, apoptosis, angiogenesis, microcirculation around hair bulb, hormones, and inflammation [ 21 ]. Numerous secondary metabolite-enriched extracts of plants/algae, such as Serenoa repens [ 22 , 23 ], Panax ginseng Mayer [ 24 ], bergamot [ 25 ], Pinus thunbergii [ 26 ], Crataegus pinnatifida [ 27 ], Aconiti Ciliare Tuber [ 28 ], Caesalpinia sappan L. [ 29 ], Ecklonia cava [ 30 ], and many others have been investigated in preclinical studies for their hair growth-promoting or hair loss-inhibiting actions. Among the biologically active substances, plant polyphenols, alkaloids, terpenoids have been identified, along with lipids and fatty acids, reviewed in [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%